PERBANDINGAN KUALITAS UDARA SEBELUM DAN SELAMA PSBB COVID-19 DI KOTA PADANG BERBASIS PENGINDERAAN JAUH - Ririn Subara Putra; Heny Mariati; Osronita Osronita (Universitas Tamansiswa Padang, 2023)
This research was conducted in the city of Padang, which is a center of mobility for the people of West Sumatra. This research is aimed at (1) Calculating the average air quality before and during the COVID-19 PSBB in Padang City (2) Classifying air quality before and during PSBB in Padang City (3) Knowing the increase in COVID-19 based on air quality in the City Padang. In this study using a descriptive method with a quantitative approach, namely correcting air quality in the city of Padang using Landsat 8 satellite image data processed with Arc Gis 10.7.1 following the air quality algorithm. The reference for this research is based on the Air Pollution Standard Index (ISPU), which is then tested differently using the Linear Regression method. The results of this study can be used as data and information for the community and government, especially for use in research on air quality during the COVID-19 pandemic. From this research, it can be seen that the air quality in Padang City, before and during the PSBB, had improved, where the air quality during the PSBB had decreased levels of PM10, SO2, and NOx.